2020
DOI: 10.3390/polym12010200
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of Polystyrene-b-Polyglycidol in Dioxane and Water/Dioxane Solutions

Abstract: In this work, the self-assembly of a series of amphiphilic polystyrene-b-polyglycidol (PS-b-PGL) diblock copolymers in dioxane and dioxane/water mixtures is presented. The PS-b-PGL have an average degree of polymerization (DP) of PS block equal to 29 units and varied degrees of polymerization for the glycidol segments with DPs of 13, 42, 69 and 117. In dioxane, amphiphilic diblock copolymers form micelles with the hydrophilic PGL placed in the core. Critical micelle concentration (CMC) was determined based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…In addition, peaks located at (166 ± 6) nm and (72 ± 3) nm are detected for the PS-b-P4VP and the PS-b-P4VP/ FeCl 3 solutions, respectively. Because the PS-b-P4VP concentration studied in the present work is well above the reported critical micelle concentration of the block copolymer, 47,48 micelles as well as their corresponding assemblies can be expected in the solution. On the basis of the contour lengths of the PS and P4VP blocks used in the present work as calculated in Table S2, the size of simple spherical micelles with a PS core and a P4VP shell would be smaller than the values detected with DLS.…”
Section: Aggregates In Solutionmentioning
confidence: 65%
“…In addition, peaks located at (166 ± 6) nm and (72 ± 3) nm are detected for the PS-b-P4VP and the PS-b-P4VP/ FeCl 3 solutions, respectively. Because the PS-b-P4VP concentration studied in the present work is well above the reported critical micelle concentration of the block copolymer, 47,48 micelles as well as their corresponding assemblies can be expected in the solution. On the basis of the contour lengths of the PS and P4VP blocks used in the present work as calculated in Table S2, the size of simple spherical micelles with a PS core and a P4VP shell would be smaller than the values detected with DLS.…”
Section: Aggregates In Solutionmentioning
confidence: 65%
“…Scheme 2a shows synthesis of linear PS-b-PGL block copolymer, whereas Scheme 2b presents further modification of the linear diblock copolymer yielding eventually copolymer PS-b-(PGL-g-PGL). The detailed description of synthesis of the diblock PS-b-PGL copolymers was described in our previous paper [27]. The description of synthesis of PS-b-(PGL-g-PGL) is described in the Materials and Methods section.…”
Section: Synthesis and Characterization Of Polystyrene-b-(polyglycidol-g-polyglycidol)mentioning
confidence: 99%
“…Similar formation of micelles and micelles aggregates was observed for linear amphiphilic copolymer PS-b-PGL in water/dioxane mixtures. It was shown that morphology of obtained aggregates was dependent on water content and hydrophobic to hydrophilic balance of the blocks in copolymer [27].…”
Section: Introductionmentioning
confidence: 99%
“…The methods of ionic polymerization of oxiranes and oxazolines, developed in our laboratory, allowed us to obtain a series of well-defined di- and triblock amphiphilic copolymers with the general structures of AB, ABA and BAB, where A is a hydrophilic block, poly(ethylene oxide), polyglycidol or poly(2-ethyl-2-oxazoline), and B is a hydrophobic block made of hydrophobically substituted polyglycidol (with ethyl, n-propyl, n-butyl, n-pentyl carbamate groups or cinnamic groups), polystyrene or poly(2-phenyl-2-oxazoline) [ 73 , 74 , 75 , 76 , 77 , 78 ]. The AB copolymers, where A is a hydrophilic polyglycidol block and B is a thermoresponsive PNIPAM [ 79 , 80 , 81 ] or pH-responsive poly(4-vinyl pyridine) (P4VP) block [ 82 ], were obtained using the combination of controlled anionic and radical polymerizations.…”
Section: Polymer Nano- and Microstructurementioning
confidence: 99%
“…With the cooperation of the CMMS PAS in Łódź, the self-assembly of amphiphilic polystyrene-b-polyglycidol copolymers (PS-b-PGL; the same hydrophobic block length and various numbers of glycidol units in the hydrophilic block) was investigated [ 77 , 78 ]. The formation of nanostructures in water after dialysis from organic solvents (dioxane and dimethylformamide) [ 77 ] and in a dioxane/water mixture [ 78 ] was followed. The morphology of the aggregates strongly depended on the initial solvent.…”
Section: Polymer Nano- and Microstructurementioning
confidence: 99%